Role of Na+ in transport of Hg2+ and induction of the Tn21 mer operon. - Selifonova, O V (1994)
The effects of sodium ions on the uptake of Hg2+ and induction of the Tn21 mer operon were studied by using Escherichia coli HMS174 harboring the reporter plasmids pRB28 and pOS14. Plasmid pRB28 carries merRT', and pOS14 carries merRTPC of the mer operon, both cloned upstream of a promoterless luciferase gene cassette in pUCD615. The bioluminescent response to 1 microM Hg2+ was significantly inhibited in E. coli HMS174(pRB28) in minimal medium supplemented with sodium ions at 10 to 140 mM. After initial acceleration, light emission declined at 50 nM Hg2+ in the presence of Na+. The mer-lux assay with resting cells carrying pRB28 and 203Hg2+ uptake experiments showed increased induction and enhanced mercury uptake, respectively, in media supplemented with sodium ions. The presence of Na+ facilitated maintenance of bioluminescence in resting HMS174(pRB28) cells induced with 50 nM Hg2+. External K+ stimulated bioluminescent response in HMS174(pRB28) and HMS174(pOS14) grown in sodium phosphate minimal medium devoid of potassium ions. Sodium ions appear to facilitate mercury transport. We propose that sodium-coupled transport of mercuric ions can be one of the mechanisms for mercury uptake by E. coli and that the Na+ gradient may energize the transport of Hg2+.